2001
DOI: 10.1021/la0103113
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions of Soluble Surfactants at a Liquid−Vapor Interface

Abstract: Although medium chain length insoluble amphiphiles are well known to form gaseous and liquid expanded phases on an air/water interface, the situation for the soluble case is less clear. We perform molecular dynamics simulations of model surfactant molecules dissolved in a bulk liquid solvent in coexistence with its vapor. Our results indicate a transition in both soluble and insoluble surfactants: a plateau in surface tension vs. surface coverage, whose instantaneous configurations display two phase coexistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…This evidence on sparingly soluble surfactants is not conclusive, however, because we do not know whether the large polar groups, which give rise to the greater solubility of the bulk soluble amphiphiles, allow a phase transition from a gaseous to a liquid state. Recent molecular dynamic simulations of model small-chain soluble surfactants interacting by van der Waals forces do demonstrate that solubility does not preclude the gas/liquid transition (50,51). The purpose of this paper is to show this is the case using the poly-ethylene glycol n-alkyl ether C 14 E 6 (CH 3 (CH 2 ) 13 (OCH 2 CH 2 ) 6 OH) as a model, fairly bulk soluble surfactant.…”
Section: Introductionmentioning
confidence: 86%
“…This evidence on sparingly soluble surfactants is not conclusive, however, because we do not know whether the large polar groups, which give rise to the greater solubility of the bulk soluble amphiphiles, allow a phase transition from a gaseous to a liquid state. Recent molecular dynamic simulations of model small-chain soluble surfactants interacting by van der Waals forces do demonstrate that solubility does not preclude the gas/liquid transition (50,51). The purpose of this paper is to show this is the case using the poly-ethylene glycol n-alkyl ether C 14 E 6 (CH 3 (CH 2 ) 13 (OCH 2 CH 2 ) 6 OH) as a model, fairly bulk soluble surfactant.…”
Section: Introductionmentioning
confidence: 86%
“…The simulations are based on standard MD techniques in an NVT (constant number of particles, volume, and temperature) statistical ensemble, 30 and the technical details of the calculation are quite similar to our previous studies of the spreading of liquids on solids and surfactant phase transitions at an air/fluid interface. 31 The basic interaction between any two particle units of type i and j is given by a LJ potential…”
Section: Surfactant Models and Simulation Methodsmentioning
confidence: 99%
“…Lin et al [6] explained the observed adsorption features of mediumchain alkanols at water/air interface by assuming the formation of small n-mers at the interface. Transitions from gaseous to liquid-like states in soluble surfactant layers have also been predicted by molecular dynamic simulation by Tomassone et al [7]. Motschmann et al investigated the equilibrium surface tension isotherm of 2-[4-(4-trifluoromethylphenylazo)phenoxy]ethane sulfonate [8].…”
Section: Introductionmentioning
confidence: 94%